The Stereotype of Batak Marriage Custom Represented in the Mursala Movie - Lambok Hermanto Sihombing (Humanitatis : Journal of Language and Literature, 2022)
Indonesia is a diverse country with a diverse range of tribes, religions, languages, and customs. Almost every region in Indonesia has its own uniqueness. Batak is one of the interesting tribes as it has unique custom to be analyzed especially their marriage custom. There are certain rules when Batak people have to find their couple. Those rules are depicted in Mursala movie. In this scientific study, the author aims to analyze the stereotype of Batak marriage represented in that movie, Mursala. In order to help the author doing this analysis, Mise En Scene approach from Manon de Reeper and Theory of Representation from Stuart Hall are used for this study. The result of this study indicates that this film represents the stereotype of Batak marriage which addresses Batak people should get married with Batak people and they are not allowed to marry the closest clan as it breaks their marriage customary law.